2020
DOI: 10.3847/2041-8213/ab911d
|View full text |Cite
|
Sign up to set email alerts
|

Tearing Instability and Periodic Density Perturbations in the Slow Solar Wind

Abstract: In contrast with the fast solar wind, which originates in coronal holes, the source of the slow solar wind is still debated. Often intermittent and enriched with low first ionization potential elements—akin to what is observed in closed coronal loops—the slow wind could form in bursty events nearby helmet streamers. Slow winds also exhibit density perturbations that have been shown to be periodic and could be associated with flux ropes ejected from the tip of helmet streamers, as shown recently by the WISPR wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 41 publications
9
53
1
Order By: Relevance
“…Therefore, this process may play a role but cannot be dominating the energy input overall. Another likely contribution to the generation of the streamer belt wind is reconnection in the near-Sun HCS (Lavraud et al 2020) triggered by a tearing mode (Réville et al 2020b). The chain of processes involved in the acceleration of the streamer belt wind, however, remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this process may play a role but cannot be dominating the energy input overall. Another likely contribution to the generation of the streamer belt wind is reconnection in the near-Sun HCS (Lavraud et al 2020) triggered by a tearing mode (Réville et al 2020b). The chain of processes involved in the acceleration of the streamer belt wind, however, remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Réville et al. (2020) demonstrated that PDSs associated with helmet streamers could be the result of the tearing mode instability at the base of the heliospheric current sheet. They argue that the larger, 10–20 hr periodicities, as well as the 1–2 hr periodicities that are observed, are all the result of the tearing mode.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also found composition signatures, which could only have come from formation at the Sun . Recent work by Réville et al (2020) demonstrated that PDSs associated with helmet streamers could be the result of the tearing mode instability at the base of the heliospheric current sheet. They argue that the larger, ∼10-20 hr periodicities, as well as the ∼1-2 hr periodicities that are observed, are all the result of the tearing mode.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%